2017
DOI: 10.3389/fnins.2017.00251
|View full text |Cite
|
Sign up to set email alerts
|

Complete Locked-in and Locked-in Patients: Command Following Assessment and Communication with Vibro-Tactile P300 and Motor Imagery Brain-Computer Interface Tools

Abstract: Many patients with locked-in syndrome (LIS) or complete locked-in syndrome (CLIS) also need brain-computer interface (BCI) platforms that do not rely on visual stimuli and are easy to use. We investigate command following and communication functions of mindBEAGLE with 9 LIS, 3 CLIS patients and three healthy controls. This tests were done with vibro-tactile stimulation with 2 or 3 stimulators (VT2 and VT3 mode) and with motor imagery (MI) paradigms. In VT2 the stimulators are fixed on the left and right wrist … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(82 citation statements)
references
References 32 publications
1
76
1
4
Order By: Relevance
“…We showed that two of three patients with CLIS could communicate using the mindBEAGLE system [8]. This is an exciting development, because BCI technology had not yet been well validated with persons with CLIS.…”
Section: Doc Assessment and Communication Platform From Gtecmentioning
confidence: 99%
“…We showed that two of three patients with CLIS could communicate using the mindBEAGLE system [8]. This is an exciting development, because BCI technology had not yet been well validated with persons with CLIS.…”
Section: Doc Assessment and Communication Platform From Gtecmentioning
confidence: 99%
“…Structural patterns will underlie it all, but dynamic patterns are essential for NCC. This is particularly important because it opens the way for direct communication with persons with severe disabilities …”
Section: Consciousness and Cognitionmentioning
confidence: 99%
“…ej., Ron-Angevin, Varona-Moya, y Silva-Sauer (2015)), ya que tienden a ofrecer un mejor rendimiento en accuracy y podrían ser un objetivo más realista para los futuros pacientes. Se debe recordar que, hasta la fecha, ningún BCI basado en P300 visual ha sido controlada por el paciente en CLIS (Guger et al, 2017). Además, el beneficio de una gran cantidad de elementos disponibles para la obtención de un buen ITR podría no ser suficiente para compensar la pérdida en accuracy, como puede verse en la sección de discusión de este artículo cuando se compara con otros trabajos.…”
Section: Conclusionesunclassified